IMPLEMENTATION OF CORPORATE MOTIVATION SYSTEM AS A DIRECTION OF FORMATION OF AN EFFECTIVE MODEL OF ORGANIZATIONAL CULTURE - VEDERNIKOV, Mykhailo; VOLIANSKA-SAVCHUK, Lesia; ZELENA, Maria; CHERNUSHKINA, Oksana; HORBATIUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the organizational culture as one of the important factors in the successful operation of the enterprise. The development of organizational culture ensures the harmonization of social and economic factors, increases the stability and competitiveness of the enterprise. A number of meaningful characteristics inherent in any organizational culture are considered. A detailed assessment of the level of corporate culture is based on the formation of a system of indicators that characterize this culture. In order to assess the level of corporate culture, expert research methods are used, which allow to give promising assessments of qualitatively new processes and phenomena that have not previously occurred in public life and about which, of course, there is no statistical information. The urgency of introduction of modern motivational technologies is considered. The experience of introduction of motivation system on key indicators at the enterprise is analyzed. The advantages of the motivation system based on the assessment of goals and KPI are determined.
Keywords: organizational culture; staff; management; motivation; monitoring; business; KPI